Development of a small molecule that corrects misfolding and increases secretion of Z α1‐antitrypsin. Issue 3 (29th January 2021) - Lomas, David A; Irving, James A; Arico‐Muendel, Christopher; Belyanskaya, Svetlana; Brewster, Andrew; Brown, Murray; Chung, Chun‐wa; Dave, Hitesh; Denis, Alexis; Dodic, Nerina; Dossang, Anthony; Eddershaw, Peter; et al.
Abstract: Severe α1 ‐antitrypsin deficiency results from the Z allele (Glu342Lys) that causes the accumulation of homopolymers of mutant α1 ‐antitrypsin within the endoplasmic reticulum of hepatocytes in association with liver disease. We have used a DNA‐encoded chemical library to undertake a high‐throughput screen to identify small molecules that bind to, and stabilise Z α1 ‐antitrypsin. The lead compound blocks Z α1 ‐antitrypsin polymerisation in vitro, reduces intracellular polymerisation and increases the secretion of Z α1 ‐antitrypsin threefold in an iPSC model of disease. Crystallographic and biophysical analyses demonstrate that GSK716 and related molecules bind to a cryptic binding pocket, negate the local effects of the Z mutation and stabilise the bound state against progression along the polymerisation pathway. Oral dosing of transgenic mice at 100 mg/kg three times a day for 20 days increased the secretion of Z α1 ‐antitrypsin into the plasma by sevenfold. There was no observable clearance of hepatic inclusions with respect to controls over the same time period. This study provides proof of principle that "mutation ameliorating" small molecules can block the aberrant polymerisation that underlies Z α1 ‐antitrypsin deficiency. Synopsis: A chemistry campaign has developed a small molecule that stabilises the severe Z deficiency mutant of α1‐antitrypsin. The lead compound binds to a cryptic pocket and blocks the conformational change and pathological polymerisation that underlie α1‐antitrypsin deficiency. A small molecule has been developed that blocks the pathological polymerisation of the Z mutant of α1‐antitrypsin. Crystallography shows that it binds to a cryptic site and negates the local effects of the Z mutation. The lead compound has good selectivity in off‐target screening. The lead compound completely blocks polymerisation and increases the secretion of Z α1‐antitrypsin 3 fold in a cell model of disease and 7 fold in a transgenic mouse model of disease. There was no effect on hepatic inclusions following 20 days of treatment. Abstract : A chemistry campaign has developed a small molecule that stabilises the severe Z deficiency mutant of α1‐antitrypsin. The lead compound binds to a cryptic pocket and blocks the conformational change and pathological polymerisation that underlie α1‐antitrypsin deficiency.